Asymmetry of chromosome Replichores renders the DNA translocase activity of FtsK essential for cell division and cell shape maintenance in Escherichia coli. - Lesterlin, C; Pages, C; Dubarry, N; Dasgupta, S; Cornet, F (2008)
Bacterial chromosomes are organised as two replichores of opposite polarity that coincide with the replication arms from the ori to the ter region. Here, we investigated the effects of asymmetry in replichore organisation in Escherichia coli. We show that large chromosome inversions from the terminal junction of the replichores disturb the ongoing post-replicative events, resulting in inhibition of both cell division and cell elongation. This is accompanied by alterations of the segregation pattern of loci located at the inversion endpoints, particularly of the new replichore junction. None of these defects is suppressed by restoration of termination of replication opposite oriC, indicating that they are more likely due to the asymmetry of replichore polarity than to asymmetric replication. Strikingly, DNA translocation by FtsK, which processes the terminal junction of the replichores during cell division, becomes essential in inversion-carrying strains. Inactivation of the FtsK translocation activity leads to aberrant cell morphology, strongly suggesting that it controls membrane synthesis at the division septum. Our results reveal that FtsK mediates a reciprocal control between processing of the replichore polarity junction and cell division.